Climate change in a small transboundary tributary of the Syr Darya calls for effective cooperation and adaptation - Stucker, D.; Kazbekov, Jusipbek S.; Yakubov, Murat; Wegerich, Kai (2012)
This article focuses on cooperative adaptation strategies at the community, water user association, district, and national levels along the Khojabakirgansai, a small transboundary tributary of the Syr Darya in Kyrgyzstan and Tajikistan. Data were collected in the basin through in-depth expert interviews, site visits, and household surveys, and were triangulated with climate change data from the available literature. Basin inhabitants cooperate on extreme events that are exacerbated by climate change, including water scarcity, droughts, and flash floods. Water demand and efficiency are key issues driven by population growth, expansion of croplands, and deteriorating canal infrastructure. Lessons learned can be considered in other small transboundary tributaries in the Ferghana Valley and Central Asia, which demonstrate how, despite the international level of tension on water issues in the region, local communities can find solutions. Cooperation, however, does not always improve the basin environment or living standards, and is likely to be strained in the coming decades by climate and population trends, among other issues.